THE CONCEPT OF A COMPREHENSIVE PROGNOSTIC MODEL OF THE EFFECTIVENESS OF IMPLEMENTATION OF MINIMALLY INVASIVE INTERVENTIONS IN THE TREATMENT OF CARIOUS PATHOLOGY - S.B. Kostenko; O.Ya. Bilynskyi; G.N. Nakashydze; M.O. Stetsyk; M.Yu. Goncharuk-Khomyn; I.V. Penzelyk (Український стоматологічний альманах, 2021)
The research presents a prognostic model of the effectiveness of minimally invasive interventions in the dental patients’ treatment of carious pathology, which was developed to reduce the impact of iatrogenic interventions, increase the results of biological, biomechanical and financial feasibility of treatment.